Analisis Environmentalisme, Religiusitas, Dan Risiko Sebagai Preferensi Minat Mahasiswa UIN Raden Mas Said Surakarta Berinvestasi Green Sukuk - Taufiq - (Pascasarjana UIN Raden Mas Said Surakarta, 2024)
Green Sukuk is a sharia-based investment that aims to preserve the earth. As a sharia investment, Green Sukuk was launched by the government after going through a process that meets sharia principles. The two types of Green Sukuk issued, namely corporate sukuk and state sukuk, have attracted investors of various ages, especially millennials and generation Z. Students as part of generation Z are an interesting object of study to be examined. Students as part of generation Z are an interesting object of study to examine the extent of student interest in green sukuk. The research was conducted on 73 students of UIN Raden Mas Said Surakarta with an explanatory quantitative method with 3 independent variables, namely environmentalism, religiosity, and investment risk and one dependent variable, namely investment interest. The results showed that the risk factor was the main factor for students to invest, while the environmentalism and religiosity factors had no effect. However, simultaneously, the three independent variables affect student interest.